The Influence of Water Immersion on the Physical and Chemical Structure of Coal. Issue 6 (26th April 2022) - Huang, Zhian; Zhao, Xinhui; Gao, Yukun; Shao, Zhenlu; Zhang, Yinghua; Liu, Xiaohan
ABSTRACT: In order to reveal the reaction mechanism responsible for the spontaneous combustion of water-immersed coal, this study researched the changes in the physical and chemical structures of coal samples before and after water immersion. The results of the specific surface and pore size analyzer test showed that compared with the original coal sample, the microporous (<10 nm) ratio decreased, but the proportion of macropores (>50 nm) increased obviously in the water-immersed coal sample. Also, as the water immersion time increased, the proportion of micropores decreased from 78.5% to 74.2%, while the proportion of macropores increased from 8.5% to 13.4%. The increase in the number of macropores increased the exposure of coal to oxygen. The scanning electron microscopy (SEM) results showed that the surface pore diameter of the water-immersed coal sample increased obviously, the surface of the coal sample was rougher, and the adsorption and diffusion of oxygen were enhanced. The Fourier transform infrared (FTIR) experiment showed that the contents of hydroxyl and aliphatic groups with higher activity in water-immersed coal samples increased significantly. The content of hydroxyl groups increased in lignite, bituminite, and anthracite by 2.7%, 2.27%, and 0.11% respectively, while the contents of aromatic hydrocarbons and oxygen-containing functional groups showed relative decreases. Compared with the original coal, the physical and chemical structure of water-immersed coal changed obviously. Therefore, it was easier for the water-immersed coal to react with oxygen, and it was also prone to spontaneously ignite.